THEORETICAL ISSUES IN FORMING THE STRUCTURE OF FINANCIAL RESOURCES FOR FINANCING INVESTMENTS IN TELECOMMUNICATIONS INFRASTRUCTURE (International Congress on Economics, Management and Business Studies, 2026)
In most cases, the issue of investing in telecommunications infrastructure is interpreted as a problem of attracting funds. In reality, however, the core of the problem lies not in the volume of funds but in their composition. This is because the same amount of investment, when financed from different sources, produces fundamentally different outcomes in terms of project value, debt burden, managerial independence, reinvestment capacity, and financial stability. In this sense, the central question in telecommunications infrastructure is not “how much resource is needed?” but rather “which types of resources should be attracted, and in what proportions?”